2018
DOI: 10.4103/jispcd.jispcd_110_18
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between agenesis of third molar and craniofacial morphology in orthodontic patients

Abstract: Aims and Objectives:The aim of this study was to evaluate the association between third molar agenesis and craniofacial morphology in a group of Iranian orthodontic patients.Materials and Methods:A total of 164 high-quality lateral cephalograms and panoramic radiographs were included in the study. Eighty-two radiographs with the absence of at least one-third molar were assigned to agenesis group and other 82 radiographic records were served as control group. Cephalometric analysis was performed, and the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, their prevalence and morphology are important to all specialties of dentistry (surgical, restorative, prosthetic, orthodontic, endodontic); many studies collected data about their presence, shape, and gender differences. Phylogenetic tendencies and changes in diet are associated with fewer teeth, with populational variations regarding the geographic region, ethnic group, gender, maxillary or mandibular jaw, craniofacial morphology, craniofacial deformities, such as cleft lip and palate, or genetic factors involved in tooth agenesis [ 1 , 2 , 3 , 4 ]. A higher incidence of agenesis among the third molars, together with a general higher prevalence in maxilla compared to mandible, has been reported for tooth number 18 in several studies [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their prevalence and morphology are important to all specialties of dentistry (surgical, restorative, prosthetic, orthodontic, endodontic); many studies collected data about their presence, shape, and gender differences. Phylogenetic tendencies and changes in diet are associated with fewer teeth, with populational variations regarding the geographic region, ethnic group, gender, maxillary or mandibular jaw, craniofacial morphology, craniofacial deformities, such as cleft lip and palate, or genetic factors involved in tooth agenesis [ 1 , 2 , 3 , 4 ]. A higher incidence of agenesis among the third molars, together with a general higher prevalence in maxilla compared to mandible, has been reported for tooth number 18 in several studies [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…For decades, orthodontists have debated the routine engagement of second molars due to the technical difficulty of bonding or banding the teeth. 2,3 However, as surgical patients have third molars that are often impacted, extracted, or absent, 4,5 second molars usually serve as the terminal teeth in the orthognathic setup. It was observed that Class III surgical patients have second molars lacking in adequate buccal root torque, 6 while Class I and II surgical patients did not share this feature.…”
Section: Introductionmentioning
confidence: 99%